Organopnictogen(iii) bis(arylthiolates) containing NCN-aryl pincer ligands: from synthesis and characterization to reactivity. Issue 27 (28th June 2022) - Duneş, Gabriel; Soran, Albert; Silvestru, Cristian
Abstract : A family of new hypercoordinated organopnictogen(iii ) di(thiolates), RPn(SC6 H3 Me2 -2, 6)2 (Pn = Sb, Bi; R = NCN-pincer ligand), has been prepared and their reactivity towards chalcogens and iodine has been investigated. Abstract : Salt elimination reactions between organopnictogen(iii ) dichlorides, RPnCl2 [R 1 = 2, 6-(Me2 NCH2 )2 C6 H3, Pn = Sb (1 ), Bi (2 ); R 2 = 2, 6-MeN(CH2 CH2 )2 NCH2 2 C6 H3, Pn = Sb (3 ), Bi (4 ); R 3 = 2, 6-O(CH2 CH2 )2 NCH2 2 C6 H3, Pn = Sb (5 ), Bi (6 )] and 2 equivalents of KSC6 H3 Me2 -2, 6 afforded the isolation of a series of new NCN-chelated monoorganopnictogen(iii ) bis(arylthiolates), RPn(SC6 H3 Me2 -2, 6)2 [R 1, Pn = Sb (7 ), Bi (8 ); R 2, Pn = Sb (9 ), Bi (10 ); R 3, Pn = Sb (11 ), Bi (12 )]. Compounds 7 and 8 are unstable upon exposure to a dry O2 atmosphere and their aerobic decomposition yields the monoorganopnictogen(iii ) oxides, cyclo -[2, 6-(Me2 NCH2 )2 C6 H3 Pn(μ-O)]2 [Pn = Sb (13 ), Bi (14 )] with concomitant formation of the corresponding disulfide, ArS–SAr (Ar = C6 H3 Me2 -2, 6). The oxidative addition of elemental sulfur or selenium to 7 undergoes a similar reaction path and gives stable heterocyclic species cyclo -[2, 6-(Me2 NCH2 )2 C6 H3 Sb(μ-E)]2 [E = S (15 ), Se (16 )]. The reaction of 12 with I2 (1 : 1 molar ratio) gives the diiodide [2, 6-O(CH2 CH2 )2 NCH2 2 C6 H3 ]BiI2 (17 ), along with the S–S oxidative coupling by-product, ArS–SAr. The use of an excess of iodine affords the crystallization of a 2 : 1 iodine adduct of 17 (17 ·0.5I2 ), built through halogen bonding. All new compounds were characterized by multinuclear NMR spectroscopy and ESI-MS as well as single crystal X-ray diffraction (except compounds 9 and 10 ).